2015
DOI: 10.1085/jgp.201511365
|View full text |Cite
|
Sign up to set email alerts
|

Beyond non-integer Hill coefficients: A novel approach to analyzing binding data, applied to Na+-driven transporters

Abstract: A novel approach to analyzing binding data from proteins with two binding sites for the same substrate provides information beyond that accessible with traditional Hill equation analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Far from being surprising, this observation leads to an important mechanistic conclusion: binding of Na + to the Na1 site increases the affinity for Na + of the Na2 site by allowing residues S353 and T354 to coordinate Na + at the Na2 site-either through a defined conformational change or by reducing the magnitude of the fluctuations, thereby increasing the population of the binding-competent conformations. In support of this conclusion, SPA Na + binding data on the S353A/T354A mutant showed that the mutant NIS has two affinities-one in the range of 1-2 mM and the other in the range of 90-120 mM (51). This finding can be interpreted as indicating that, in the double mutant, the cooperative interactions are lost, yielding a highaffinity Na1 site and a disrupted Na2 site (51).…”
Section: Q263n (20%)mentioning
confidence: 71%
See 4 more Smart Citations
“…Far from being surprising, this observation leads to an important mechanistic conclusion: binding of Na + to the Na1 site increases the affinity for Na + of the Na2 site by allowing residues S353 and T354 to coordinate Na + at the Na2 site-either through a defined conformational change or by reducing the magnitude of the fluctuations, thereby increasing the population of the binding-competent conformations. In support of this conclusion, SPA Na + binding data on the S353A/T354A mutant showed that the mutant NIS has two affinities-one in the range of 1-2 mM and the other in the range of 90-120 mM (51). This finding can be interpreted as indicating that, in the double mutant, the cooperative interactions are lost, yielding a highaffinity Na1 site and a disrupted Na2 site (51).…”
Section: Q263n (20%)mentioning
confidence: 71%
“…In support of this conclusion, SPA Na + binding data on the S353A/T354A mutant showed that the mutant NIS has two affinities-one in the range of 1-2 mM and the other in the range of 90-120 mM (51). This finding can be interpreted as indicating that, in the double mutant, the cooperative interactions are lost, yielding a highaffinity Na1 site and a disrupted Na2 site (51).…”
Section: Q263n (20%)mentioning
confidence: 71%
See 3 more Smart Citations